Visualization Psychology - Albers Szafir, Danielle; Borgo, Rita.; Chen, Min.; Edwards, Darren J.; Fisher, Brian; Padilla, Lace. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book designates Visualization Psychology as an interdisciplinary subject. The book contains literature reviews and experimental works that exemplify a range of open questions at this critical intersection. It also includes discourses that envision how the subject may be developed in the coming years and decades. The field of visualization is a rich playground for discovering new knowledge in both visualization and psychology. As visualization techniques augment human cognition, these techniques must be developed and improved by building on theoretical, empirical and methodological knowledge from psychology. At the same time, visualization processes surface numerous phenomena about interactions between the human mind and digital entities, such as data, visual imagery, algorithms, and computer-generated predictions and recommendations. Visualization psychology is a new type of science in the making.
Foreword -- Preface -- Part I: Visualization Psychology from a Psychology Perspective -- 1 Color Semantics for Visual Communication -- 2 Theories and Models in Graph Comprehension -- 3 Mental Models and Visualization -- 4 Improving Evaluation using Visualization Decision-Making Models: A practical Guide -- 5 Supporting Diverse Research Methods for Observing Huge Variable Space in Empirical Studies for Visualization -- Part II:Visualization Psychology from a Visualization Perspective -- 6 Visualization Onboarding Grounded in Educational Theories -- 7 Adaptive Visualization of Health Information Based on CognitivePsychology - Scenarios, Concepts and Research Opportunities -- 8 Design Cognition in Data Visualization -- 9 Visualization Psychology: Foundations for an Interdisciplinary -- 10 Visualization Psychology for Eye Tracking Evaluation -- 11 Task Matters When Scanning Data Visualizations -- 12 Perceptual Biases in Scatterplot Interpretation -- 13 Leveraging Conscientiousness-Based Preferences inInformation Visualization Design -- 14 Visualizing Uncertainty in Different Domains: Commonalities and Potential Impacts on Human Decision Making -- 15 Analysis of Sensemaking Strategies: Psychological Theories in Practice.
Keywords: User interfaces (Computer systems).; Human-computer interaction; Cognitive psychology; Information visualization; User Interfaces and Human Computer Interaction; Cognitive Psychology; Data and Information Visualization